Multidimensional crop improvement by ILRI and partners: Drivers, approaches, achievements, and impact - Blümmel, Michael; Samireddypalle, Anandan; Zaidi, Pervez Haider; Vadez, Vincent; Ramana Reddy, Y.; Janila, Pasupuleti (CAB International, 2020)
This chapter reviews the findings, outputs and outcomes of research on multidimensional crops in the tropics, focusing mainly on cereals and grain legumes. Specifically, the chapter addresses the: (i) establishment of crop residues (CRs) as traded commodities and their changing valuation as the impetus for multidimensional crop improvement; (ii) trait identification and development of infrastructure for quick and affordable phenotyping for CR fodder quality; (iii) exploitation of existing cultivar-dependent variations in CR fodder quality; (iv) targeted genetic enhancement for multitrait food-feed-fodder cultivars; (v) trade-offs between CR fodder traits and primary traits, notably grain and pod or straw yields; and (vi) outcomes of multidimensional crop improvement and future work.